SPECIFICS OF BIOAMINE STATUS IN INFANTS AND PRESCHOOL CHILDREN WITH ASTHMA - M.A. Smirnova; L.I. Mozzhukhina; E.V. Shubina; V.N. Fedorov (Педиатрическая фармакология)
Bronchial asthma tops the listing of chronic respiratory diseases in children. It was verified that mediators (histamine, serotonin, dopamine, adrenaline, noradrenaline) have influence on the specific nature of bronchial asthma in infants and pre-school children. 121 children (68 patients with bronchial asthma, 23 with relapsing obstructive bronchitis and 30 healthy children) were examined in the course of the study. The results obtained suggest that changes in biogenic amines correlate not only with the disease period and severity but also depend on the nature of the anti-inflammatory therapy. Key words: biogenic amines, bronchial asthma, relapsing obstructive bronchitis, children. (Pediatric Pharmacology. – 2010; 7(5):94-96)